2012
DOI: 10.1371/journal.ppat.1002522
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Highly Neuroinvasive Prion Strains

Abstract: Infectious prions propagate from peripheral entry sites into the central nervous system (CNS), where they cause progressive neurodegeneration that ultimately leads to death. Yet the pathogenesis of prion disease can vary dramatically depending on the strain, or conformational variant of the aberrantly folded and aggregated protein, PrPSc. Although most prion strains invade the CNS, some prion strains cannot gain entry and do not cause clinical signs of disease. The conformational basis for this remarkable vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 71 publications
4
73
5
Order By: Relevance
“…3A). Similar strain plasticity has been observed in other neurodegenerative diseases (1,27,28,(33)(34)(35)(36). Considering the quite different and more malleable appearance of the hSOD1 fibrils in vitro (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…3A). Similar strain plasticity has been observed in other neurodegenerative diseases (1,27,28,(33)(34)(35)(36). Considering the quite different and more malleable appearance of the hSOD1 fibrils in vitro (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…This coexistence distinguishes the hSOD1 D90A mice from previous disease models where the variation of strains is typically observed between individuals (1,34,35,41). Even so, the hSOD1 D90A mice highlight the notion that strain variation influences pathology, as previously observed for prions (27,28), and in patients and models for synucleopathies (33), Alzheimer's disease (1,35,36), and tauopathies (34).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The category 2 agent (e.g., the C413 agent) is characterized by low to intermediate levels of PK-resistant PrP on initial passage, higher specific infectivity, lower amyloidogenicity, and increased compatibility with wt PrP C , thereby allowing efficient propagation in mice expressing either anchorless or wt PrP C . The second category also templates PrP res conformers with lower stability that may correspond to agents with increased fitness (7,17,34). The relationship between fitness and stability is under debate for hamster scrapie strains (3).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sedimentation profiles and protease sensitivity have been used as indirect markers of PrP Sc structure and have shown a correlation with strain-specific transmission properties (22)(23)(24)(25)(26)(27). More recently, studies with rodent-adapted, cloned prion strains demonstrated that also the conformational stability of PrP Sc , measured indirectly either by inducing a progressive denaturation of the protein with the chaotropic salt guanidine hydrochloride (GdnHCl) or by exposing the protein to increasing temperatures in the presence of sodium dodecyl sulfate (SDS), may vary among different strains (28)(29)(30). Attempts have also been made to correlate PrP Sc conformational stability to strain-specific properties such as replication rates, although with conflicting, opposite results in murine and hamster models (28)(29)(30).…”
mentioning
confidence: 99%